Analisis Asesmen Pembelajaran PPKn Daring Kelas II SDN Plintahan 1 Dan SDN Durensewu 1 - Miftakhul Romzah; Sutarno Sutarno; Khusnul Khotimah; Miftakhul Romzah; Sutarno Sutarno (Universitas Negeri Malang, 2021)
Abstract: The purpose of this study is to analyze the planning and implementation of online Civics learning assessment in class II at SDN Plintahan 1 and SDN Durensewu 1 located in Pasuruan Regency. This study used qualitative descriptive research. The subjects of this study were second grade teachers at SDN Plintahan 1 and SDN Durensewu 1. The methods used in this study were observation, interviews, and documentation methods. Data analysis was carried out to draw conclusions from the online Civics learning assessment. The results of this study indicate that the teacher has planned an assessment in the form of a written test in planning the assessment of the cognitive domain, planning an assessment in the form of observation in the planning of the assessment of the affective domain, and did not plan a performance assessment in the planning of the assessment of the psychomotor domain. In practice, the teacher assesses the cognitive domain by giving written tests to students, but it is not in accordance with the lesson plans, the teacher assesses the affective domain by assessing the timeliness of students in collecting assignments and seeing the neatness of students' writing, and the teacher does not assess the psychomotor domain because it takes time. long and difficult to do during a pandemic. Abstrak: Penelitian ini bertujuan ini menganalisis perencanaan dan pelaksanaan asesmen pembelajaran PPKn daring kelas II di SDN Plintahan 1 dan SDN Durensewu 1 yang berlokasi di Kabupaten Pasuruan. Penelitian ini menggunakan rancangan deskriptif kualitatif. Subjek penelitian ini adalah guru kelas II SDN Plintahan 1 dan SDN Durensewu 1. Metode yang digunakan dalam penelitian ini adalah metode observasi, wawancara, dan dokumentasi. Analisis data dilakukan untuk menarik kesimpulan dari asesmen pembelajaran PPKn daring. Hasil penelitian ini menunjukkan bahwa guru telah merencanakan penilaian berupa tes tulis pada perencanaan asesmen ranah kognitif, merencanakan penilaian berupa observasi pada perencananaan asesmen ranah afektif, dan tidak merencanakan penilaian kinerja pada perencanaan asesmen ranah psikomotor. Dalam pelaksanaannya, guru melakukan asesmen ranah kognitif dengan memberikan tes tulis kepada siswa, namun tidak sesuai dengan RPP, guru melakukan asesmen ranah afektif dengan menilai ketepatan waktu siswa dalam mengumpulkan tugas dan melihat kerapian tulisan siswa, dan guru tidak melakukan asesmen ranah psikomotor karena membutukan waktu yang lama dan sulit dilakukan pada masa pandemi.